Quantitative Assessment of Temporal Changes in Subaqueous Hydrothermal Activity in Active Crater Lakes During Unrest Based on a Time-Series of Lake Water Chemistry - Terada, Akihiko; Yaguchi, Muga; Ohba, Takeshi (Frontiers in Earth Science, 2022)
Regular sampling of lake water has been performed at many volcanoes to assess the state of volcanic activity. However, it is not clear whether the absolute concentrations or, instead, rate of changes in concentrations are more suitable for such assessments. In this study, we show that temporal changes in concentrations of an element in lake water are described by a simple differential equation, assuming changes in lake volume and chemical processes are negligible. The time constants (63% response time for changes in the chemical concentration in lake water) have a wide range varying between 20 and 1,000 days for the studied volcanoes in Japan, meaning it takes a long time to assess volcanic activity based on the absolute concentration of an element. In order to assess the volcanic activity in a shorter time period, based on a time-series of lake element concentration data, we developed a numerical model to calculate temporal changes in the steady-state concentration, which is proportional to the elemental concentrations of the bulk hydrothermal fluid injected from subaqueous fumaroles and hot springs. We applied our method to Yugama crater lake at Kusatsu–Shirane volcano, Japan, and quantitatively evaluated temporal changes in the hydrothermal input from 1964 to 2020. As a result, we detected changes in the Cl concentrations of the bulk hydrothermal input that were associated with unrest including the phreatic eruption in 1976 and earthquake swarms in 1989–1992 and 2014–2020. The future concentration in the lake water can be predicted from the most recent steady-state concentrations. Comparing the predicted concentration curve with the concentration obtained from lake water samples, it is possible to quickly assess whether the concentration of the bulk hydrothermal input has increased/decreased or remained constant.